Cardiac development in the chick embryo with reference to conduction and structure using a myosin heavy chain knock down model and global RNA sequencing in an outflow tract banded model - Parnall, Matthew (2018)
In the developing embryo the heart is the first organ to develop and thus supply the rest of the developing embryo with a good blood supply. Regulation of cardiogenesis in these early stages of development is key as any dysregulation will result in defects in the heart. Dysregulation of sarcomeric proteins has been associated with a range of cardiomyopathies and septal defects. This demonstrates the importance of structure on development. However, structural genes have not been linked to conduction disorders in the heart. Myosin heavy chain genes (MYH) encode sarcomeric structural proteins (MHC). Previous work by Rutland et al. (2011) showed that alpha myosin heavy chain (αMHC), beta myosin heavy chain (βMHC) and embryonic myosin heavy chain (eMHC) are necessary for correct Ca2+ transients, with eMHC also required for a normal action potential and normal intracellular K+. The thesis uses a chick model to analyse the effect of structure on the conduction system. The first part of the thesis utilises antisense oligonucleotide morpholino technology for gene knockdown (KD) of the mRNA of αMCH, βMHC and eMHC proteins to analyse the effect on structure and conduction in the heart. Cultures of atrial and ventricular KD HH29 cells showed no differences in beating rate, though 2 out of 9 samples of αMYH and eMYH culture failed to form beating syncytiums, compared to all controls that did. The structural maturity of KD cultures was assessed through Z-disc integrity by immunocytochemistry. Decreased maturity of both the atria and ventricular culture was found KDs. Expression of selected conduction genes was also assed with the pace maker cell potassium channel HCN4 showing decreased levels at the sinus venosus region by in situ hybridisation and significant decreases by RT-qPCR in whole chick heart embryos at HH20. The decrease in expression of such genes could be caused by disruption to internal cell architecture that organises expression of proteins at the cell membrane. Structure at the Z-disc, which show immaturity in KD hearts, is key for this process. Altered haemodynamics and cardiomyopathy is known to effect internal heart structure and the next phase of the project utilised an out flow tract banding (OFT-banding) technique that has been shown previously to alter haemodynamics, effect heart structure and show features of cardiomyopathy. Global sequencing was carried out in order to assess the effect that OFT-banding may have on the conduction system in HH29 chick embryos. In order to carry out global gene expression on OFT-banded hearts, a library preparation method was optimised that removed excess haemoglobin from the hearts and an >99% reduction in all embryonic globin genes was seen, this then allowed detailed gene analysis even of low read genes by RNA sequencing. Sequencing revealed differential expression of calcium sequestering genes in what appears to be a conductive cardioprotective mechanism to maintain coordinated contraction. Interestingly, sequencing also revealed a gene profile that would be expected to alter AMPK signalling that could lead to a multitude of disorders or affects such glycogen storage cardiomyopathy or increased inhibition of myosin expression.